Inhibition of the FixL Sensor Kinase by the FixT Protein inSinorhizobium meliloti - Garnerone, Anne-Marie; Cabanes, Didier; Foussard, Marie; Boistard, Pierre; Batut, Jacques (The Journal of biological chemistry, 1999)
Nitrogen fixation in symbiotic rhizobia is subject to multiple levels of gene regulation. In Sinorhizobium meliloti, the alfalfa symbiont, the FixLJ two-component regulatory system plays a major role in inducing nitrogen fixation and respiration gene expression in response to the low ambient O2 concentration of the nodule. Here we report on the mode of action of the FixT protein, a recently identified repressor of nitrogen fixation gene expression in S. meliloti. First, we provide evidence that FixT prevents transcription of the intermediate key regulatory genes nifA and fixK by counteracting the activity of the FixLJ two-component system under otherwise inducing microoxic conditions. Second, we demonstrate that FixT acts as an inhibitor of the sensor hemoprotein kinase FixL, preventing the production or the accumulation of its phosphorylated form. FixT is thus a new example of a regulatory protein that blocks signal transduction in two-component systems at the level of the sensor kinase.